Temozolomide in glioblastoma treatment: 15-year clinical experience and analysis of its efficacy - Glavatskyi, O.Ya.; Zemskova, O.V.; Khmelnytskyi, H.V.; Kardash, K.A.; Shuba, I.M.; Stuley, V.A. (PH Akademperiodyka, 2023)
Summary. Aim: To analyze retrospectively the efficacy of temozolomide (TMZ) in various treatment regimens in glioblastoma patients accounting for varying parameters of their treatment. Materials and Methods: 302 glioblastoma patients were treated at the State Institution “Romodanov Institute of Neurosurgery of the National Academy of Medical Sciences of Ukraine” from 2003 through 2017. All the patients were surgically treated. In 205 patients, the surgery was followed by adjuvant radiotherapy (RT) with concomitant TMZ (RT + TMZ group). In 97 patients, the surgery was followed by adjuvant RT only (RT group). Kaplan — Meier survival analysis with log-rank test and Cox proportional hazards regression analysis were used for comparing overall survival (OS) and recurrence-free survival (RFS) depending on the age and gender of the patients, the extent of tumor resection, the chemotherapy intensity and the type of RT. Results: In RT + TMZ group as a whole, OS median was 20.7 months vs 10.8 months in RT group (р < 0.0001). The RFS was 14.8 months vs 7.9 months, correspondingly (р < 0.0001).The survival did not depend on the age, gender or localization of the tumor. On the contrary, the intensity of CTX (the number of TMZ cycles in adjuvant mode), the extent of tumor resection, and the type of RT were among the factors affecting significantly OS and RFS. The improvement in OS and RFS with increasing number of the maintenance TMZ courses was more significant in the patients aged below 60. The use of stereotactic conformal mode for RT provides an advantage in the survival over the conventional RT in RT + TMZ group. Conclusions: The combination of concomitant and adjuvant maintenance CTX with TMZ was the most effective CTX regimen affecting positively OS and RFS.